Breast Amide Proton Transfer Imaging at 3 T: Diagnostic Performance and Association With Pathologic Characteristics. Issue 3 (11th July 2022) - Liu, Zhou; Wen, Jie; Wang, Meng; Ren, Ya; Yang, Qian; Qian, Long; Luo, Honghong; Feng, Sha; He, Cuiju; Liu, Xin; Wu, Yin; Luo, Dehong
Abstract : Background: Amide proton transfer (APT) imaging has been increasingly applied in tumor characterization. However, its value in evaluating breast cancer remains undetermined. Purpose: To assess the diagnostic performance of APT imaging in breast cancer and its association with prognostic histopathologic characteristics. Study Type: Prospective. Subjects: Eighty‐four patients with breast lesions. Field Strength/Sequence: A 3.0 T/single‐shot fast spin echo APT imaging. Assessment: APTw signal in breast lesion was quantified. Lesion malignancy, T stage, grades, Ki‐67 index, molecular biomarkers (estrogen receptor [ER] expression, progesterone receptor [PR] expression, human epidermal growth factor receptor [HER‐2] expression), molecular subtypes (luminal A, luminal B, triple negative, and HER‐2 enriched) were determined. Statistical Tests: Student t ‐test, one‐way analysis of variance, receiver operating characteristic analysis, and Pearson's correlation with P  < 0.05 as statistical significance. Results: APTw signal was significantly higher in malignant lesions (1.55% ± 1.24%) than in benign lesions (0.54% ± 1.13%), and in grade III lesions than in grade II lesions (1.65% ± 0.84% vs. 0.96% ± 0.96%), and in T2‐ (1.57% ± 0.64%) and T3‐stage lesions (1.54% ± 0.63%) than in T1‐stage lesions (0.81% ± 0.64%) for invasive breast carcinoma of no special type. APTw signal significantly correlated with Ki‐67 index ( r  = 0.364) but showed no significant difference in groups of ER ( P  = 0.069), PR ( P  = 0.069), HER‐2 ( P  = 0.961), and among molecular subtypes ( P  = 0.073). Data Conclusion: APT imaging shows potential in differentiating breast lesion malignancy and associates with prognosis‐related tumor grade, T stage, and proliferative activity. Evidence Level: 2 Technical Efficacy: Stage 2